The hidden salmon patch: ocular lymphoma mistaken as Vogt Koyanagi disease - Nazima SA,; Muhaya M,; Kok, HS; Hazlita Mohd Isa, (Faculty of Medicine, UKM Medical Centre, 2016)
Ocular inflammation from various causes may have similar clinical presentation thus careful clinical evaluations are mandatory particularly when the disease appear to be resistant to treatment. This paper reports a case of ocular lymphoma which was initially treated as Vogt Koyanagi Harada disease at a different centre. A 65-year-old Sudanese man complained of gradual worsening left eye vision. Careful ocular and slit lamp examination revealed a conjunctival lesion with choroidal infiltration as well as exudative retinal detachment. Computed tomography scan (CT scan) showed left eye axial proptosis, and a homogenous enhancing mass at the posterior coat of the globe. Tissue biopsy of the conjunctival lesion revealed marginal Zone B cell (MALT type), low grade, non-Hodgkin’s lymphoma. AS the ocular signs and symptoms progressed, chemotherapy was initiated. The proptosis, exudative retinal detachment, disc hyperemia and swelling improved after chemotherapy. The post treatment CT scan showed reduction of the posterior ocular coat mass. The possibility of malignant lymphoma should be considered in patients with resistant uveitis despite administration of corticosteroid. Ocular lymphoma is an indolent tumour with good prognosis. Careful ocular examination, adequate imaging studies followed by early surgical biopsy will contribute to early diagnosis.